2009
DOI: 10.3732/ajb.0800254
|View full text |Cite
|
Sign up to set email alerts
|

Transmitting tissue architecture in basal‐relictual angiosperms: Implications for transmitting tissue origins

Abstract: Carpel transmitting tissue is a major floral innovation that is essential for angiosperm success. It facilitates the rapid adhesion, hydration, and growth of the male gametophyte to the female gametophyte. As well, it functions as a molecular screen to promote male gametophytic competition and species-specific recognition and compatibility. Here, we characterize the transmitting tissue extracellular matrix (ECM) and pollen tube growth in basal-relictual angiosperms and test the hypothesis that a freely flowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 178 publications
(323 reference statements)
1
37
0
1
Order By: Relevance
“…High temperature, pollen germination, tube growth and ovule development, and ovule penetration by pollen tubes Successful pollen germination on the stigma and growth of the pollen tube to the female gametophyte to deliver sperm is dependent on cell-to-cell interactions between the pollen grain/tube and transmitting tissues (stigma, style, and ovary; Sage et al, 2009;Chae and Lord, 2011). In comparison to anther and pollen development, few studies have examined the effect of HT on transmitting tissue and ovule development and in vivo post-pollination events.…”
Section: High Temperature Anther Dehiscence and Pollen Dispersalmentioning
confidence: 99%
“…High temperature, pollen germination, tube growth and ovule development, and ovule penetration by pollen tubes Successful pollen germination on the stigma and growth of the pollen tube to the female gametophyte to deliver sperm is dependent on cell-to-cell interactions between the pollen grain/tube and transmitting tissues (stigma, style, and ovary; Sage et al, 2009;Chae and Lord, 2011). In comparison to anther and pollen development, few studies have examined the effect of HT on transmitting tissue and ovule development and in vivo post-pollination events.…”
Section: High Temperature Anther Dehiscence and Pollen Dispersalmentioning
confidence: 99%
“…However, in both angiosperms and gymnosperms, ecm of the female reproductive organs should provide specific ions and molecules necessary for nutrition, attraction and guidance of the male gametophyte. Many studies in angiosperms have shown that the pollen–pistil interaction involves such ecm components as homogalacturonan, arabinogalactan proteins and calcium ions (Cheung et al 1995; Jauh and Lord 1996; Mollet et al 2000; Lenartowska et al 2001; Zhao et al 2004; Bednarska et al 2005; Hristova et al 2005; Coimbra et al 2007; Ge et al 2009; Sage et al 2009; Costa et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the differentiation of a transmitting tissue within the carpel that supports pollen tube growth to the ovule has long been viewed as promoting male competition and increasing maternal choice of sperm donors (7,8). The formation of callose plugs within pollen tubes recently has been hypothesized to have enabled male gametophytes to grow at higher rates and compete over greater distances than was the case for the immediate ancestors of angiosperms (8,9).…”
mentioning
confidence: 99%
“…Finally, the evolution of insect pollination in conjunction with the early diversification of floral morphology and anatomy are widely viewed to have led to increased levels of pollen reception and hence, male-male competition (4). Collectively, the evolution of the carpel, extragynoecial compitum, transmitting tissue, callose plugs, and insect pollination seems to have resulted in significantly enhanced levels of prefertilization male competition and maternal choice, and thus may have played a major role in the early diversification of angiosperms (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%